2010
DOI: 10.1177/0013124510379619
|View full text |Cite
|
Sign up to set email alerts
|

High School Students and Their Lack of Preparedness for College: A Statewide Study

Abstract: In this study, the authors examined the college-ready graduate rates of all students ( n = 1,099 high schools) in the State of Texas for the 2006-2007 school year. Data were analyzed for students’ scores in reading, in math, and in both subject areas combined. Approximately one-third of all students were determined to be college-ready in both subject areas. Statistically significant and practically relevant differences, reflecting moderate to large effect sizes, were present in reading, math, and both subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…In addition, the overall scores obtained by these groups of students generally declined during this 16-year period. The results of this study mirror the conclusions of Klopfenstein (2010) and Moore and Slate (2011). In contrast, Klopfenstein (2010) and Moore and Slate (2011) argued that AP course-taking alone may not affect time to degree.…”
Section: Relationship To Literaturesupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the overall scores obtained by these groups of students generally declined during this 16-year period. The results of this study mirror the conclusions of Klopfenstein (2010) and Moore and Slate (2011). In contrast, Klopfenstein (2010) and Moore and Slate (2011) argued that AP course-taking alone may not affect time to degree.…”
Section: Relationship To Literaturesupporting
confidence: 84%
“…Specifically, dramatic increases in the number of Hispanic students who took AP English exams in each of the three states were documented in the current study. In contrast, Klopfenstein (2010) and Moore and Slate (2011) argued that AP course-taking alone may not affect time to degree. Some researchers (e.g., Dounay, 2006;Eyring, 2011;Palaich et al, 2006;Santoli, 2002) have suggested that accelerated learning options such as AP courses allow students to graduate from college in less time and thereby save money on college tuition.…”
Section: Relationship To Literaturementioning
confidence: 99%
“…It is essential for both postsecondary institutions and high schools to establish collaborative efforts for student success. Collaborative efforts would create an environment that enhances student preparedness by aligning academic and social expectations required by postsecondary institutions (Moore et al, 2010). Today, school counselors are overwhelmed with an extensive workload and are unable or unwilling to persuade students away from college.…”
Section: Existing Literaturementioning
confidence: 99%
“…The argument in favour of adults from business and industry supporting school students through mentoring programmes is partly attributable to the observation that most secondary students graduate from school ill-prepared for FE/HE or the world of work (Hall 2003;Moore et al 2010). This is because a considerable proportion of a secondary teacher's time is spent teaching specific discrete academic subjects, rather than supporting the development of the whole person (Reid 2002).…”
Section: Introductionmentioning
confidence: 99%